Aluminum-magnesium-silicon alloy with low natural aging and high formability as well as preparation method and application of aluminum-magnesium-silicon alloy
By adjusting the element content and process flow in aluminum-magnesium silicon alloy, the challenges of 6xxx aluminum alloy in natural aging and forming performance are solved, and low natural aging and high forming properties are achieved, which is suitable for the production of automotive panels and structural parts.
Patent Information
- Application Number
- CN202411859840.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-28
AI Technical Summary
The 6xxx aluminum alloy has natural aging during room temperature storage, resulting in an increase in hardness, affecting the forming performance, and insufficient forming limits, making it difficult to prepare complex structural parts.
Using low natural aging and high-forming aluminum-magnesium silicon alloys, natural aging and magnesium silicon alloys are adjusted by adjusting the content and proportion of elements such as Mg, Si, Sn, Cu, Ti, etc., combined with semi-continuous casting, homogenized heat treatment, hot rolling, cold rolling and solid solution quenching heat treatment, natural aging is suppressed and forming capacity is improved.
It significantly suppresses natural aging, refines alloy grains, improves the forming capacity of Al-Mg-Si alloy, and is suitable for the production of automotive interior and exterior plates and structural parts, achieving low-cost industrial production.
Smart Images

Figure CN119710391A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of aluminum alloy materials, and in particular relates to an aluminum-magnesium-silicon alloy with low natural aging and high formability, a preparation method and an application thereof. Background Art
[0002] In order to achieve energy conservation and emission reduction, the use of aluminum plates to replace the steel plates commonly used in traditional car bodies is an important way to achieve lightweight car bodies. Heat-treatable and strengthened 6xxx series (Al-Mg-Si(-Cu)) aluminum alloys have become the preferred aluminum alloys for car body exterior panels due to their high specific strength, excellent corrosion resistance, high weldability, and good formability. At the same time, they belong to the same alloy system as the most widely used architectural aluminum materials in my country, which is very beneficial for waste recycling and the development of a circular economy.
[0003] In order to make 6xxx series aluminum alloys meet the performance requirements of aluminum alloys for vehicle bodies, the hardness of 6xxx series aluminum alloys is required to be low before stamping to ensure that no cracks are generated during bending. However, after quenching by the material manufacturer, the 6000 series aluminum alloys are inevitably stored at room temperature for a period of time before being stamped in the vehicle factory. This causes the sheet to undergo obvious natural aging during this period, which increases the hardness before stamping, which is not conducive to bending forming. More importantly, the aluminum alloy sheet for the vehicle body is required to have a good forming limit and be able to prepare various complex structural parts. Therefore, poor forming is the main challenge faced by the application of aluminum alloy automotive sheets. At present, the main industrial 6xxx series aluminum alloys for vehicle bodies are mainly pre-aged to reduce the adverse effects of natural aging, and the forming limit is mainly improved by alloying and optimizing the process to weaken the texture to improve the formability of aluminum alloys. Therefore, suppressing the adverse effects of natural aging and improving the forming limit are key issues in promoting the application of 6xxx series aluminum alloys for automotive bodies. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide an aluminum-magnesium-silicon alloy with low natural aging and high formability, a preparation method and an application thereof, which can significantly inhibit natural aging, refine the alloy recrystallized grains, and at the same time improve the forming ability of the Al-Mg-Si alloy, is suitable for use as automotive inner and outer panels and structural parts, and can achieve low-cost industrial production.
[0005] An embodiment of the present invention provides an aluminum-magnesium-silicon alloy with low natural aging and high formability, comprising the following components in weight percentage, Mg: 1.0-1.8%, Si: 0.6-1.5%, Cu: 0.1-0.35%, Sn: 1.0-1.5%, Ti: 0.05%-0.15%, the remainder is Al, and Sn / Mg is 0.8-1.2.
[0006] Preferably, Sn / Mg is 0.9 to 1.1.
[0007] Preferably, the components are included in the following weight percentages: Mg: 1.4-1.6%, Si: 0.6-1.5%, Cu: 0.15-0.25%, Sn: 1.2-1.3%, Ti: 0.05%-0.15%, and the balance is Al, and Sn / Mg is 0.8-1.2.
[0008] Preferably, the components include the following weight percentages: Mg: 1.41%, Si: 0.8%, Cu: 0.2%, Sn: 1.3%, Ti: 0.07%, and the balance is Al, and Sn / Mg is 0.92.
[0009] Preferably, in the aluminum-magnesium-silicon alloy, Fe≤0.5%, Mn≤0.2%, and Cr≤0.1%.
[0010] The embodiment of the present invention provides a method for preparing the aluminum-magnesium-silicon alloy with low natural aging and high formability, comprising the following steps: 1) Melting, casting, and obtaining ingots; Specifically: pure aluminum, pure magnesium, Al-Sn and Al-Si master alloys are selected; a semi-continuous casting method is adopted to rapidly cool from the liquidus temperature to the solidus temperature in a crystallizer at a cooling rate of not less than 100°C / min to inhibit the formation of coarse grains.
[0011] 2) Homogenization heat treatment: heat the ingot to 520-580°C at a rate of 20-60°C / h and keep it at that temperature for 3-24 hours, or heat the ingot to 440-500°C at a rate of 20-60°C / h and keep it at that temperature for 2-10 hours, and then heat it to 520-580°C and keep it at that temperature for 3-24 hours; Homogenization treatment can eliminate dendrites produced during the melting and casting process, promote the uniform diffusion and distribution of alloy elements, promote the transformation of AlFeSi phase from lamellar to spherical, and improve the mechanical properties of the alloy. The homogenization temperature is generally selected from 520℃-580℃. If the homogenization temperature exceeds 580℃, the alloy is at risk of overburning. When the homogenization temperature is low, the insulation time is prolonged, which is not conducive to production efficiency. When the homogenization temperature is high, the insulation time can be appropriately reduced. The preferred homogenization system is 540℃ insulation for 20 hours and then air cooling.
[0012] 3) Hot rolling: control the total reduction rate to not less than 75%, and the final rolling temperature to be controlled at 320-360 ℃; If the final rolling temperature is lower than 320 °C, intermediate annealing is performed at 350-420 °C; Intermediate annealing can ensure recrystallization before cold rolling, ensuring that the alloy has sufficient plasticity without cracking during the rough rolling process. The homogenized ingot is kept in a 420℃-460℃ heating furnace for 2-3 hours before hot rolling, and the plate is rolled to a thickness of 2-10mm. Intermediate annealing helps to eliminate the work hardening caused by hot rolling, and regulates the phase distribution and texture in the alloy to improve formability. The hot-rolled plate is placed in a 400℃-450℃ heat treatment furnace for 2-3 hours and then cooled with the furnace.
[0013] 4) Cold rolling, the total cold rolling reduction rate is controlled at 60-90%; Cold rolling can accumulate deformation energy for subsequent solid solution recrystallization, refine the recrystallized grains, and improve the surface quality of the plate. The cold rolling reduction rate is preferably 60-90%, and the plate after intermediate annealing is cold rolled to a thickness of 1.2 mm.
[0014] 5) Solution quenching heat treatment: 540-580 °C for 10-600 s, using room temperature water spray or water pool quenching cooling method to ensure that the quenching cooling rate is not less than 10 °C / s to obtain aluminum-magnesium-silicon alloy; Solution quenching treatment is a key process to improve alloy performance. High-temperature solution dissolves Mg, Si and Sn solute atoms into the aluminum matrix. The solution temperature is generally selected between 540°C and 580°C. The solubility of Sn decreases significantly as the solution temperature decreases, and has a maximum solubility at around 570°C. Because the present invention preferably uses a solution temperature of 570°C, the holding time is selected to be 5-10 minutes to ensure that all solute atoms are dissolved into the aluminum matrix. However, if the holding time is too long, the grains will grow significantly, which is not good for the alloy performance. The preferred holding time is 5 minutes. After the solution treatment, the alloy is quenched by spray cooling, cooled to room temperature at the fastest cooling rate to form a supersaturated solid solution, and placed at room temperature for natural aging.
[0015] 6) Allow to age naturally.
[0016] Preferably, the homogenization heat treatment is: heating the ingot to 540-560°C at a rate of 30-50°C / h and keeping it warm for 12-24 h, or heating the ingot to 450-480°C at a rate of 30-50°C / h and keeping it warm for 6-8 h, and then heating it to 540-560°C and keeping it warm for 12-24 h.
[0017] Preferably, the intermediate annealing treatment is performed by cooling the steel sheet to 250° C. in the furnace and then air cooling the steel sheet to room temperature.
[0018] Preferably, the solution quenching heat treatment is carried out at 550-570°C for 200-400 seconds.
[0019] An embodiment of the present invention provides an application of the aluminum-magnesium-silicon alloy with low natural aging and high formability, which is used as an inner and outer panel or structural part of an automobile.
[0020] The roles of the various elements of the present invention in the aluminum alloy are as follows.
[0021] Mg and Si are the main alloying elements of Al-Mg-Si alloy, which can constitute Mg2Si strengthening phase. After solution quenching treatment, the alloy forms a series of metastable phases such as Mg2Si during artificial aging, which strengthens the alloy. With the increase of Mg2Si content in the equilibrium alloy, the density of β" phase increases and the distribution is more uniform during aging, which increases the strength of the alloy. Excessive Si in the alloy can promote the precipitation of a large amount of β" phase, and the β" phase is evenly distributed, which makes the structure refined and improves the strength of the alloy. At the same time, excessive Si is easy to enrich at the grain boundary and increase the intergranular corrosion sensitivity of the alloy. Considering that the impurity Fe will also consume part of Si, the amount of Si added is increased to 0.8%~1.5%. In addition to participating in the formation of β" phase, excessive Mg can interact with Sn to form coarse Mg2Sn phase.
[0022] Sn can effectively inhibit the natural aging of the alloy only in the form of solid solution atoms in the alloy. According to the solubility of Sn at different temperatures in the Al-Sn phase diagram, and considering that the addition of Mg and Si will reduce the maximum solid solubility of Sn in the alloy, Sn exceeding the solid solubility will form a coarse Mg2Sn phase with Mg in the alloy, and excessive Sn will consume too many Mg atoms in the alloy and reduce the Mg content in the alloy. The range of Sn addition needs to be strictly controlled. The present invention controls the Sn / Mg mass ratio between 0.8 and 1.2, which is the key to the present invention.
[0023] Adding Cu to Al-Mg-Si alloy can effectively promote aging precipitation and increase the aging hardening rate of the alloy, but at the same time it significantly increases the sensitivity to intergranular corrosion, which is detrimental to the corrosion resistance of the alloy. Therefore, the Cu addition range in the alloy is controlled at 0.1~0.35%.
[0024] Fe is an impurity element in Al-Mg-Si, which is not conducive to the formability of the alloy. The Fe content in the alloy is strictly controlled to ensure that Fe ≤ 0.5%.
[0025] Although adding a small amount of Cr and Mn can form a dispersed phase, improve the shape and distribution of the AlFeSi phase, and be beneficial to the formability of the alloy, adding excessive Cr and Mn will form coarse Al6Mn and Al7Cr, which is detrimental to the formability. Considering that adding Mn and Cr will reduce the solubility of Sn, Mn and Cr are not added to the alloy of the present invention, and Mn is controlled to be ≤ 0.2% and Cr ≤ 0.1%.
[0026] Ti acts as a heterogeneous core for crystal nucleation of grains during melt casting and solidification in Al-Mg-Si alloys, refining the alloy grains. However, adding too much Ti will form coarse TiAl3 in the alloy, affecting the mechanical properties of the alloy. Therefore, the Ti content is controlled between 0.05% and 0.15%. The beneficial effect of the present invention is that by adding excessive Sn to the Al-Mg-Si alloy, the maximum amount of Sn atoms are dissolved into the aluminum matrix by adjusting the Sn / Mg ratio, so that Sn obtains the maximum solid solubility. By controlling the Sn / Mg ratio in the alloy, the excessive Sn and Mg form a coarse Mg2Sn phase, induce the PSN effect, refine the grain structure in the alloy, and improve the formability of the alloy, which is suitable for use as automotive inner and outer panels and structural parts, and enhances the core competitiveness of the company's new products. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is the IPF diagram of Comparative Example 1 of the present invention.
[0028] Figure 2 This is the IPF diagram of Example 1 of the present invention.
[0029] Figure 3 This is a scanning electron microscope image of Comparative Example 1 of the present invention.
[0030] Figure 4 This is a scanning electron microscope image of Example 1 of the present invention.
[0031] Figure 5 The graph shows the change of alloy strength of Example 1 of the present invention and Comparative Example 1 with natural aging time. DETAILED DESCRIPTION
[0032] Example 1 A low natural aging and high formability aluminum-magnesium-silicon alloy, the alloy consists of the following components by mass percentage: Mg: 1.02%, Si: 0.62%, Sn: 1.0%, Cu: 0.2%, Ti: 0.08%, Fe in the alloy is controlled to be ≤ 0.5%, Mn ≤ 0.2%; Cr ≤ 0.1%, and the balance is Al.
[0033] A method for preparing an aluminum-magnesium-silicon alloy with low natural aging and high formability is as follows: 1. 99.98% industrial pure aluminum, pure Mg, Al-10Sn and Al-30Si master alloy are used as raw materials, added into a resistance melting furnace for melting, and then a semi-continuous casting method is used to prepare an ingot with a size of 210 mm (length) * 150 mm (width) * 55 mm (height); 2. The ingot is then cut and milled, and the cut ingot is homogenized. The homogenization heat treatment method is: the ingot is heated to 550°C at a rate of 40°C / h and kept warm for 20 hours.
[0034] 3. Hot rolling: Hot rolling is carried out on a Φ500 two-roll hot rolling unit, with a starting rolling temperature of 460°C, a final rolling temperature controlled at 320-360°C, and a total reduction rate of not less than 75%. If the final rolling temperature is lower than 320°C, the plate is kept at 420°C for 2 hours and then subjected to intermediate annealing (cooled to 250°C in the furnace and then air-cooled to room temperature) to ensure recrystallization before cold rolling.
[0035] 4. Cold rolling: The total cold rolling reduction rate is controlled at 80%.
[0036] 5. Solution quenching heat treatment: keep at 550℃ for 300s, use room temperature water spray or water pool quenching cooling method to ensure that the quenching cooling rate is not less than 10℃ / s to obtain aluminum-magnesium-silicon alloy.
[0037] 6. Place at room temperature for natural aging, and then form after 14 days of natural aging.
[0038] The content of each element in the alloy was adjusted according to the method in Table 1 to obtain multiple examples and comparative examples. The preparation methods of these examples and comparative examples are the same as those shown in Example 1.
[0039] The proportions of the products of the embodiments of the present invention and the comparative examples are shown in Table 1.
[0040] Table 1 Component content ratio of different products
[0041] Table 2 Mechanical properties of alloys after different natural aging
[0042] In summary, the larger the N value, the stronger the drawing ability and the better the stamping performance; the larger the r value of the plate, the lower the wrinkling tendency, the stronger the plate's resistance to thinning, and is conducive to stamping. Trace amounts of Sn can inhibit natural aging, and inhibiting natural aging is related to bending performance. Trace amounts of Sn addition cannot increase the r value and N value. Adding excessive amounts of Sn and Mg not only inhibits natural aging, but also forms a large number of coarse particles due to excessive Sn addition. Under the action of PSN, the grains are significantly refined and the texture is weakened, thereby increasing the elongation r value and N value. It can be seen from the data in Table 2 that the total N value and r value of the embodiments of the present application are significantly higher than those of the comparative examples. The aluminum alloy of the present invention has obvious resistance to natural aging and high formability, and is suitable for automotive exterior covers.
[0043] A person skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of protection of the present application is limited to these examples. In line with the concept of the present application, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of different aspects of one or more embodiments of the present application as described above, which are not provided in detail for the sake of simplicity.
[0044] One or more embodiments of the present application are intended to cover all such substitutions, modifications and variations that fall within the broad scope of the present application. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of one or more embodiments of the present application should be included in the protection scope of the present application.
Claims
1. A low natural aging and high formability aluminum-magnesium-silicon alloy, characterized in that: The invention comprises the following components in weight percentage: Mg: 1.0-1.8%, Si: 0.6-1.5%, Cu: 0.1-0.35%, Sn: 1.0-1.5%, Ti: 0.05%-0.15%, the balance is Al, and Sn / Mg is 0.8-1.
2.
2. The low natural aging and high formability aluminum-magnesium-silicon alloy according to claim 1, characterized in that: Sn / Mg is 0.9~1.
1.
3. The low natural aging and high formability aluminum-magnesium-silicon alloy according to claim 1, characterized in that: The invention comprises the following components in weight percentage: Mg: 1.4-1.6%, Si: 0.6-1.5%, Cu: 0.15-0.25%, Sn: 1.2-1.3%, Ti: 0.05%-0.15%, the balance is Al, and Sn / Mg is 0.8-1.
2.
4. The low natural aging and high formability aluminum-magnesium-silicon alloy according to claim 1, characterized in that: The steel sheet includes the following components in weight percentage: Mg: 1.41%, Si: 0.8%, Cu: 0.2%, Sn: 1.3%, Ti: 0.07%, and the balance is Al. The Sn / Mg ratio is 0.
92.
5. The low natural aging and high formability aluminum-magnesium-silicon alloy according to any one of claims 1 to 4, characterized in that: Control the content of Fe≤0.5%, Mn≤0.2%, and Cr≤0.1% in aluminum-magnesium-silicon alloy.
6. A method for preparing an aluminum-magnesium-silicon alloy with low natural aging and high formability as claimed in any one of claims 1 to 5, characterized in that: The following steps are included: 1) Melting, casting, and obtaining ingots; 2) Homogenization heat treatment: heat the ingot to 520-580°C at a rate of 20-60°C / h and keep it at that temperature for 3-24 hours, or heat the ingot to 440-500°C at a rate of 20-60°C / h and keep it at that temperature for 2-10 hours, and then heat it to 520-580°C and keep it at that temperature for 3-24 hours; 3) Hot rolling: control the total reduction rate to not less than 75%, and the final rolling temperature to be controlled at 320-360 ℃; If the final rolling temperature is lower than 320 °C, intermediate annealing is performed at 350-420 °C; 4) Cold rolling, the total cold rolling reduction rate is controlled at 60-90%; 5) Solution quenching heat treatment: 540-580 °C for 10-600 s, using room temperature water spray or water pool quenching cooling method to ensure that the quenching cooling rate is not less than 10 °C / s to obtain aluminum-magnesium-silicon alloy; 6) Allow to age naturally.
7. The preparation method according to claim 6, characterized in that: The homogenization heat treatment is as follows: heating the ingot to 540-560°C at a rate of 30-50°C / h and keeping it warm for 12-24 hours, or heating the ingot to 450-480°C at a rate of 30-50°C / h and keeping it warm for 6-8 hours, and then heating it to 540-560°C and keeping it warm for 12-24 hours.
8. The preparation method according to claim 6, characterized in that: The intermediate annealing treatment method is to cool to 250°C in the furnace and then take it out and air cool it to room temperature.
9. The preparation method according to claim 6, characterized in that: The method of solution quenching heat treatment is: keeping at 550-570 ℃ for 200-400 s.
10. An application of the low natural aging and high formability aluminum-magnesium-silicon alloy as claimed in any one of claims 1 to 5, characterized in that: Used as interior and exterior panels or structural parts of automobiles.